♤ Moderators
⭐ Branily star
❤️ other best user
Question <<<
please answer this question urgently fast answer
no spam
no spam
no spam
Attachments:
Answers
Answered by
2
Explanation:
4s
2
−4s+1
Factorize the equation, we get(2s−1)(2s−1)
So, the value of 4s
2
−4s+1 is zero when 2s−1=0,2s−1=0, i.e., when s=
2
1
or s=
2
1
.
Therefore, the zeros of 4s
2
−4s+1 are
2
1
and
2
1
.
Now,
⇒Sum of zeroes =
2
1
+
2
1
=1=−
4
−4
=−
Coefficient of s
2
Coefficient of s
⇒Product of zeros =
2
1
×
2
1
=
4
1
=
4
1
=
Coefficient of s
2
Constant term
Answered by
2
Hey buddy!
Given polynomial
On factorising :-
So the zeros are -1 and 5/4
Verification of their coefficients and zeros
Sum of the zeros :-
=> coefficient of x/coffeicient of x² = (-1) + (5/4)
=> -1/4 = -1/4
And also,
Product of zeros :-
=> constant term/coefficient of x² = (-1)*(5/4)
=> -5/4 = -5/4
Hence verified!!
Similar questions